Жарким летом: рассказы / Ф. А. Абрамов - Абрамов Федор Александрович (Советский писатель, 1984)
Экземпляры: ф.9 (1984) / Инвентарный номер: 8109 / Цена: 1.20 / Сис.шифр: 84(2Рос=Рус)6 / Авт.знак: А 16 / ГРНТИ: 17.82 / ББК: 84(2Рос=Рус)6-44